Materials characterization. - Bruno, Thomas J.; Deacon, Ryan; Jansen, Jeffrey A.; Magdefrau, Neal; Mueller, Erik M.; Vander Voort, George F.; Yang, Dehua (Materials scientist) (ASM Handbook, 2019)
"The 2019 edition of 'ASM handbook, Volume 10: Materials characterization' provides detailed technical information that will enable readers to select and use analytical techniques that are appropriate for their problem. Each article describing a characterization technique begins with an overview of the method in simplified terms and lists common applications as well as limitations. Sample size, form, and special preparation requirements are listed upfront to help readers quickly decide if the techniques are appropriate to solve their problem. Tables and charts listing the most common characterization methods for different classes of materials are included in the beginning of the handbook. The tables give information on whether the technique is suitable for elemental analysis, qualitative analysis, surface analysis, or alloy verification. The articles also describe material characterization in general terms according to material type and serve as a jumping off point to the more specific technique articles."--